Lived experience of depression in women living with Human Immunodeficiency Virus in Gondar City health facilities, Northwest, Ethiopia: A phenomenological study - Tadele Amare Zeleke; Tadesse Awoke Ayele; Zewditu Abdissa Denu; Lillian Mwanri; Telake Azale (PLoS ONE, 2026)
Background Many women living with HIV (WLHIV) in worldwide experience mental health conditions, particularly depression, which can negatively affect their overall wellbeing. Their lived experiences play a crucial WLHIV has been explored in various global context, there is limited research focusing on the specific women’s lived experience of depression in Ethiopia. Understanding these experience is essential to inform the development of culturally appropriate and targeted mental health interventions and support system. Method A qualitative phenomenological design was employed to explore women’s lived experience of depression in Ethiopia. Criterion-based sampling was used, and recruitment continued until data saturation was achieved. Data were collected through in-depth face to face interviews with 16 participants attending health facilities. An inductive approach was used for analysis, with code derived from the data using Ritchie and Spencer’s analytical framework. Subsequently, Interpretive Phenomenological Analysis was applied to identify key themes and subthemes. Data analysis was supported by MAXQDA (version 22) software. Results This study identified key themes on women’s lived experience of depression, including symptoms, meaning, perceived causes, perpetuating and relieving factors, treatment perceptions, coping strategies, and challenges. Depression affected emotional, physical and social well-being, and was shaped by factors such as HIV status, stigma, financial hardship, and lack of support. Women used diverse coping strategies, including spiritual practices, social support, and daily routines. Some preferred spiritual healing over professional care. Depression also negatively affected memory, motivation, self-care, and ART adherence, contributing to isolation, unemployment, and decline health. Conclusion Depression among WLHIV shaped by intersecting social, economic, and health related challenge. Addressing this requires the Ministry of Health to implement integrated, culturally sensitive mental health interventions and strengthen mental health awareness, combining psychosocial support, spiritual care, and improved access to professional services.